Luciferases with Tunable Emission Wavelengths. (9th October 2017) - Hiblot, Julien; Yu, Qiuliyang; Sabbadini, Marina D.B.; Reymond, Luc; Xue, Lin; Schena, Alberto; Sallin, Olivier; Hill, Nicholas; Griss, Rudolf; Johnsson, Kai
Abstract: We introduce luciferases whose emission maxima can be tuned to different wavelengths by chemical labeling. The luciferases are chimeras of NanoLuc with either SNAP‐tag or HaloTag7. Labeling of the self‐labeling tag with a fluorophore shifts the emission maximum of NanoLuc to that of the fluorophore. Luciferases with tunable colors have applications as reporter genes, for the construction of biosensors and in bioimaging.